Psycho-social perspectives on mental health and well-being - Padmanaban, Srinivasan 1971-; Subudhi, Chittaranjan 1989- (IGI Global, 2020)
"This book examines the physical, social, and emotional aspects of mental health and well-being"--Provided by publisher